Towards the implementation of integrated information system (IIS) in construction : a study on knowledge, awareness and perception among professionals / Handzalah Abdullah @ Sudin - Abdullah @ Sudin, Handzalah (2000)
The new millennium offers a wide range of opportunities for the construction industry. The transition from information to knowledge era is beginning to take place in the new globalised world where IT is the enabling mechanism. However, the potential benefits of IT utilisation is not so recognised in the Malaysian construction industry. It is well known that the industry has lagged behind others in harnessing the full potentials of information technology.